2021
DOI: 10.1590/s1517-707620210004.1389
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of implantable drug delivery technology: poly (3-hydroxybutyrate) / polypropylene glycol films containing simvastatin

Abstract: Natural polymers have attracted much attention in recent years for the study of new drug delivery systems. These materials are used as polymer matrices to protect the active drug from degradation in the biological environment and to improve the release kinetics of the drug. The poly(3-hydroxybutyrate) (PHB) is a natural biocompatible polymer, widely used in combination with other polymers to improve their physicochemical properties. Thus, this work aimed to develop and characterize films of PHB and blends cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…Moreover, a great amount of SIM (25%) also can influence the nanoparticles sizes. In a recently published study by our grup [35] , the presence of 25% of SIM in PHB/ PPG films leaded to instability of the PHB/PPG films which, in a way, corroborates the results of this research.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, a great amount of SIM (25%) also can influence the nanoparticles sizes. In a recently published study by our grup [35] , the presence of 25% of SIM in PHB/ PPG films leaded to instability of the PHB/PPG films which, in a way, corroborates the results of this research.…”
Section: Discussionsupporting
confidence: 91%
“…The investigation of the release of an insecticide from PHB/PCL microspheres showed that the release rate was favored by the addition of PCL to the blend suggesting the possibility of modulating the release rate by formulating blend [19] . Therefore, in the present study, it can be proposed that both the release from the nanospheres and SIM occur predominantly by diffusion, but also by erosion of the polymer matrix [35] .…”
Section: Discussionmentioning
confidence: 72%